1981
DOI: 10.1002/1097-0142(19810215)47:4<649::aid-cncr2820470405>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Combined modality therapy of operated astrocytomas grade III and IV. Confirmation of the value of postoperative irradiation and lack of potentiation of bleomycin on survival time: A prospective multicenter trial of the scandinavian glioblastoma study group

Abstract: In a controlled, prospective, randomized investigation, started in 1974, 118 patients with supratentorial astrocytoma Grade III--IV were divided into three groups. Groups 1 and 2 received 45 Gy postoperatively to the whole supratentorial brain. Bleomycin in 15-mg doses and a total dose of 180 mg or placebo was given intravenously three times a week, one hour prior to radiotherapy, during weeks 1, 2, 4 and 5. Group 3 received conventional care but no radiotherapy or chemotherapy. Median survival rates of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0
9

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(128 citation statements)
references
References 4 publications
5
113
0
9
Order By: Relevance
“…A key question is whether the results presented here are consistent with clinical experience and in particular the clinical outcomes in patients undergoing radiotherapy. Multiple studies have demonstrated an overall survival benefit for postoperative radiation therapy after surgical resection compared with surgery alone in the management of newly diagnosed glioblastoma multiforme (GBM) (34)(35)(36). In addition, the response of GBM tumors to radiation predicts the patient lifespan after treatment.…”
Section: Ir Induces Cytotoxic Type I Ifnmentioning
confidence: 99%
“…A key question is whether the results presented here are consistent with clinical experience and in particular the clinical outcomes in patients undergoing radiotherapy. Multiple studies have demonstrated an overall survival benefit for postoperative radiation therapy after surgical resection compared with surgery alone in the management of newly diagnosed glioblastoma multiforme (GBM) (34)(35)(36). In addition, the response of GBM tumors to radiation predicts the patient lifespan after treatment.…”
Section: Ir Induces Cytotoxic Type I Ifnmentioning
confidence: 99%
“…Median duration of survival after surgery and radiation in various series has been reported to be 24 months for anaplastic astrocytoma and 9 months for glioblastoma (Walker et al, 1978(Walker et al, , 1980Kristiansen et al, 1981;Chang et al, 1983;Green et al, 1983). Addition of chemotherapy has increased median survival to approximately 11 months for glioblastoma (Walker et al, 1978(Walker et al, , 1980Chang et al, 1983;Green et al, 1983).…”
Section: Does Surgical Resection Prolong Survival?mentioning
confidence: 99%
“…With modern treatment paradigms the median survival time of patients with the most malignant glioma, glioblastoma multiforme (GBM), has increased from several months to over a year in selected series (Walker et al, 1978;Kristiansen et al, 1981;Gutin et al, 1991). Survival in patients with other intracranial primary neoplasms and metastatic disease has likewise increased.…”
Section: Introductionmentioning
confidence: 99%